Metastatic Squamous cell carcinoma of small bowel with occult primary presented as small bowel obstruction - M., Sridhar Reddy; M., Naresh; Rath, Alok (International Surgery Journal, 2018)
Metastatic lesions in the small bowel are more common than primary lesions and account for 0.5% of all small intestinal malignancies. Most common is malignant melanoma followed by adenocarcinoma from pancreas, colon or stomach; and squamous cell carcinoma from lung, cervix, esophagus, skin, penis, ovary, pancreas and gallbladder. Gastrointestinal involvement as a manifestation of metastatic squamous cell carcinoma with unknown primary is relatively uncommon with very few being reported in the literature. The most common presenting symptom of small bowel lesions is subacute or acute obstruction and less commonly, bowel perforation, abdominal pain or hemorrhage. It is a diagnosis which dawns upon after the surgery when histopathology proves the same and therefore a thorough workup to establish the primary starts after the bailout procedure. Its clinical course is aggressive, characterized by a short preclinical history, resistance to chemotherapy, and overall dismal prognosis with a median life expectancy of 6 to 9 months as it represents a disseminated disease.